2004
DOI: 10.1515/bc.2004.069
|View full text |Cite
|
Sign up to set email alerts
|

Metalloproteases with EGF, CUB, and thrombospondin-1 domains function in molting of Caenorhabditis elegans

Abstract: Functional analysis using RNAi was performed on eleven genes for metalloproteases of the M12A family in Caenorhabditis elegans and the interference of the C17G1.6 gene (nas-37) was found to cause incomplete molting. The RNAi of the C26C6.3 gene (nas-36) also caused a similar molting defect but not so severely as that of the nas-37 gene. Both the genes encode an astacin-like metalloprotease with an epidermal growth factor (EGF)-like domain, a CUB domain, and a thrombospondin-1 domain, in this order. The promote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 18 publications
1
44
0
Order By: Relevance
“…C. elegans DPY-31 was found to be expressed throughout the life-cycle in the hypodermal cells (Novelli et al 2004) and in the oesophageal glands (Stepek et al 2010b), whereas the heterologous expression of the B. malayi promoter/ reporter gene revealed predominant expression in the oesophageal gland cells and gut of C. elegans, leading to the suggestion that DPY-31 plays a role in the construction of the nematode cuticle (Stepek et al 2010b). Although the current study does not examine the expression pattern of NAS-36 from C. elegans, previous studies have described this expression also to be in the hypodermal cells (Suzuki et al 2004). Davis et al (2004) showed that NAS-37 from C. elegans was abundantly expressed in the excretory duct and in the oesophagus and also in the hypodermal cells of the cuticle 4 h prior to each moult.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…C. elegans DPY-31 was found to be expressed throughout the life-cycle in the hypodermal cells (Novelli et al 2004) and in the oesophageal glands (Stepek et al 2010b), whereas the heterologous expression of the B. malayi promoter/ reporter gene revealed predominant expression in the oesophageal gland cells and gut of C. elegans, leading to the suggestion that DPY-31 plays a role in the construction of the nematode cuticle (Stepek et al 2010b). Although the current study does not examine the expression pattern of NAS-36 from C. elegans, previous studies have described this expression also to be in the hypodermal cells (Suzuki et al 2004). Davis et al (2004) showed that NAS-37 from C. elegans was abundantly expressed in the excretory duct and in the oesophagus and also in the hypodermal cells of the cuticle 4 h prior to each moult.…”
Section: Discussionmentioning
confidence: 68%
“…In addition, some of these enzymes are found to be secreted from the glandular system that surrounds the oesophagus and may be particularly important in the latter stages of cuticle removal or ecdysis, with many representing important components of the moulting exsheathment fluid (Albertson and Thomson, 1976;Nelson et al 1983;Bird, 1987). Many of the subgroup V nematode astacin metalloproteases share these cuticle-related expression patterns, i.e., they are found in the excretory duct, pharynx and hypodermal cells (Davis et al 2004;Novelli et al 2004;Suzuki et al 2004;Stepek et al 2010b). C. elegans DPY-31 was found to be expressed throughout the life-cycle in the hypodermal cells (Novelli et al 2004) and in the oesophageal glands (Stepek et al 2010b), whereas the heterologous expression of the B. malayi promoter/ reporter gene revealed predominant expression in the oesophageal gland cells and gut of C. elegans, leading to the suggestion that DPY-31 plays a role in the construction of the nematode cuticle (Stepek et al 2010b).…”
Section: Discussionmentioning
confidence: 99%
“…So far, the regulatory mechanisms of C. elegans molting are not yet understood, although about a dozen genes have been identified that lead to molting defects when mutated. These genes can be classified into five categories based on their possible functions: (1) proteases that are used to degrade the old cuticle, including a cathepsin Z-like cysteine protease (Cecpz-1) (Hashmi et al, 2004), and two metalloproteases, nas-36 and nas-37 (Davis et al, 2004;Suzuki et al, 2004); (2) transcriptional regulators, including nhr-23 (Kostrouchova et al, 1998(Kostrouchova et al, , 2001, nhr-25 (Asahina et al, 2000;Gissendanner and Sluder, 2000), and let-19 (Wang et al, 2004); (3) enzymes involved in cholesterol metabolism such as let-767 (Kuervers et al, 2003) or cholesterol transporters such as lrp-1 (Yochem et al, 1999); (4) molecules involved in secretion and extracellular transport such as sec-23 (Roberts et al, 2003) and CeVps-27 (Roudier et al, 2005); (5) others, such as the angiotensin converting enzyme-like non-peptidase acn-1 (Brooks et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Positive regulators of molting include matrix metalloproteases (Davis et al 2004;Hashmi et al 2004;Suzuki et al 2004;Altincicek et al 2010;Kim et al 2011;Stepek et al 2011), which are important for digestion of the old cuticle or processing of the new cuticle precursors, as well as selenoproteins, which promote collagen cross-linking (Stenvall et al 2011). Other functional classes of molecules critical for molting include sterol-binding nuclear hormone receptors (NHRs) (Kostrouchova et al 1998(Kostrouchova et al , 2001Gissendanner and Sluder 2000;Hayes et al 2006;Monsalve and Frand 2012), enzymes controlling sterol and fatty acid synthesis (Jia et al 2002;Kuervers et al 2003;Entchev and Kurzchalia 2005;Li and Paik 2011), and hedgehog-related proteins (Zugasti et al 2005;Hao et al 2006), which are often modified by sterols (Wendler et al 2006) and are dependent on NHRs for expression (Kouns et al 2011).…”
mentioning
confidence: 99%